Modeling of lithium-ion battery for energy storage system simulation - Chen, ShuaiXun. (2009)
Battery models for simulation are useful for estimating operating life, stability, and related characteristics of batteries used in circuits and systems. This report presents a dynamic model of lithium-ion battery. The model accounts for nonlinear equilibrium potentials, rate- and temperature-dependencies, thermal effects and responses to transient power demand. In this project, the author developed a lithium-ion battery model from the mathematical equations given in a research paper [I]. Simulation using SIMPLORER software was performed. The charge and discharge characteristics of the model were obtained and the results were compared to a battery manufacturer’s data of a Sony US 18650 lithium-ion battery cell and the experimental data of an UltraLife UBBL10 Lithium-ion battery system. Simulation results of the lithium battery model agreed well with the manufacturer’s data in all the static characteristics. The model can be easily modified to fit parameters from different batteries and can be extended for wide dynamic ranges of different temperatures and current rates. The model also can be used in parallel and in series. The simulation results are nearly the same as experimental data.